Species status of Bombus monticola Smith (Hymenoptera: Apidae) supported by DNA barcoding - Gjershaug, Jan Ove; Staverløkk, Arnstein; Kleven, Oddmund; Ødegaard, Frode (Zootaxa, 2013)
Certain species of bumblebees are difficult to distinguish based on morphology alone due to a lack of diagnostic characters and extensive intraspecific variation in colour patterns. The discussion concerning whether Bombus lapponicus and Bombus monticola are the same species or not, seems to be ongoing. We present a study of 16 speciemens of B. monticola/B. lapponicus from Norway, identified with previously published morphological characters and with DNA barcoding. The results showed a match with the examination of the morphological characters and the DNA sequence data. These results confirm that B. lapponicus and B. monticola appear as separate species in Norway, which supports earlier conclusions based on both morphological differences and differences in cephalic marking pheromones in males. The wide sympatric range of the two taxa in Scandinavia also strongly support their species status.